Analisis Quality of Service (QoS) Jaringan Internet di Kampus 4 Universitas Garut Berdasarkan Standar TIPHON - Rengga Andrea Pakarnada; Akhmad Fauzi Ikhsan; Irman Nurichsan (Fakultas Teknik Universitas Garut, 2026)
The Internet plays an important role in supporting academic and operational activities at Campus 4 of Universitas Garut, particularly for inter-faculty activities, seminars, and live streaming events. This study analyzes the Quality of Service (QoS) performance of the internet network using Wireshark for direct measurement and NS-2 for network simulation. The evaluation was conducted at three locations, namely the Administration Room (BAK), Auditorium, and Rooftop, during academic and non-academic days using QoS parameters including throughput, packet loss, delay, and jitter based on the TIPHON standard. The results show that during academic days, the BAK Room achieved a throughput of 447.8 Kbps, packet loss of 0.493%, delay of 20.487 ms, and jitter of 20.488 ms, while the Auditorium and Rooftop showed better performance with a good category. During non-academic days, network performance improved significantly, with throughput values of 1.044 Kbps in the BAK Room, 3.29 Mbps in the Auditorium, and 13.5 Mbps in the Rooftop, categorized as good to excellent. Overall, the network quality was classified as good, with an average QoS index of 3.75 or 94.75%. The NS-2 simulation results showed a similar trend to the Wireshark measurements. This study recommends increasing bandwidth capacity, implementing bandwidth management, and optimizing network usage to improve the quality of campus internet services.